Investigação do mecanismo de ação antidepressivo-símile da quercetina em camundongos por meio de testes comportamentais e neuroquímicos - Carvalho, Bernardo Hollanda de (2018)
Depression is a serious and disabling psychiatric disorder with a high incidence in the population. The treatment involves drugs that possesses undesired effects and in many cases, decreases the patient's adherence to the treatment. This fact has encouraged the search for new drugs and the vegetable kingdom has been widely investigated in this sense. Flavonoids are an important class of secondary metabolites found in different plant species. Quercetin (3, 5, 7, 3 '- 4' pentahydroxy flavone),is one of the most abundant flavonoids in the human diet, it has has several biological activities such as: anti-inflammatory, anti-aggregating, antihypertensive, diabetic, anxiolytic and antidepressant. This last activity, however, is still not well characterized and this fact led to the development of the present study, which aimed to evaluate the antidepressant-like effect of quercetin, through behavioral and neurochemical tests. Male Swiss mice (CEUA / UFPB protocol 112/2016) were used, from the Animal Production Unit of the Federal University of Paraíba - UPA / UFPB. The animals were divided into groups composed of six mice, which were orally treated with saline, quercetin 10 and 40 mg / kg and intraperitoneally with imipramine 30 mg / kg and subjected to open field and forced swimming tests. For the purpose of investigating the possible mechanism of action, quercetin was administered alone (0.5 mg / kg, v) and in combination with antidepressants bupropion (0.1 mg / kg, ip), fluoxetine (0.1 mg / kg , ip) and imipramine (1 mg / kg, ip) in animals submitted to forced swimming. In addition, neurochemical analyzes were performed to determine the striatal concentration of monoamines and the hippocampal concentration of nitrite and TBARs. The results showed that the administration of quercetin did not alter the locomotor activity of the animals submitted to the open field; on the other hand, the compound in question significantly and dose-dependently reduced the immobility time of animals in the forced swimming. This effect was potentiated in the presence of bupropion and imipramine, but not of fluoxetine. Treatment with quercetin (10 mg / kg, v.o.) did not change the hippocampal concentration of nitrite and TBARs, two important markers of oxidative stress. Finally, oral administration of flavonoid significantly increased the concentration of noradrenaline, but not dopamine, in the striatum of animals subjected to the forced swimming test. Taken together, the results suggest that the antidepressant-like effect of quercetin seems to depend, at least in part, on the increase in the striatal concentration of monoamines, especially noradrenaline.